Glucagon-like peptide-2 reduces the obesity-associated inflammation in the brain - Domenico Nuzzo; Sara Baldassano; Antonella Amato; Pasquale Picone; Giacoma Galizzi; Gaetano Felice Caldara; Marta Di Carlo; Flavia Mulè (Neurobiology of Disease, 2019)
Growing evidence suggests a link between obesity and neurodegeneration. The purpose of the present study was to explore the neuroprotective potential of glucagon-like peptide-2 (GLP-2) in the brain of high fat diet (HFD)-fed mice. Markers of inflammation and oxidative stress were analysed in the brains of obese mice chronically treated with [Gly2]-GLP-2 (teduglutide), the stable analogue of the GLP-2, and they were compared to age-matched untreated obese and lean animals. Neurodegeneration was examined by TUNEL assay. HFD feeding increased the expression of pro-inflammatory mediators (NF-kB, IL-8, TNF-α, IL-1β and IL-6), glial fibrillary acidic protein (GFAP), index of gliosis and neurodegeneration, stress marker proteins (p-ERK, Hsp60 and i-NOS), amyloid-β precursor protein (APP). [Gly2]-GLP-2 treatment significantly attenuated the HFD-induced increased expression of the various markers, as well as the higher levels of reactive oxygen species found in brains of untreated-HFD mice. Immunofluorescence confirmed that the increase of GFAP or APP in the brain cortex of HFD mice were less prominent in the [Gly2]-GLP-2 treated group. TUNEL-positive cell number in brain sections of [Gly2]-GLP-2-treated HFD-fed mice was significantly lesser in comparison with untreated-HFD animals and similar to STD fed mice. In conclusion, the results of the present study suggest that GLP-2 stable analogue improves the obesity-associated neuroinflammation and the central stress conditions, it reduces the neuronal apoptotic death, providing evidence for a neuroprotective role of the peptide.